Communicative orthoepic nature of the motivational utterance in the Yakut Language - Egorovich Alekseev, Ivan; Nikolaevna Sorova, Irina (Revista de la Universidad del Zulia, 2019)
The article analyzes the main structural-semantic and functional features of the motivational phrase in the Yakut language. Through the experimental linguistic analysis of the speech signal, the intonational nature of certain types of motivating phrases, such as call, order and demand is characterized.